Study on Dynamics Characteristics of Multilayer Plates Impacted by Hemispherical Projectile - Noryuzleen Azam, Muhamad Norhaziem; Ibrahim, Mohd Norihan (Research Progress in Mechanical and Manufacturing Engineering, 2022)
The multilayer plate is normally used in many applications as a form of protection and also to enhance the strength and capability of any structure in automotive, aerospace and military industry. The study conducted is related to effect on the interaction and collision of projectile towards multilayer target plate at normal impact. Numerical study has been carried out by using ANSYS explicit finite element method. The analysis is focused on the failure mode and deformation of the multilayer target plate. The preliminary contact and the post perforation of multilayer target plate were observed and the contour mode of failure was identified. The kinematic motion of projectile toward multi layers target plates occur at different range of impact velocity of 300 m/s up to 700 m/s. The multilayer target plate involved in this study is Al2024 T4 and Steel 1006 respectively. The numerical simulation on the deformation and failure mode of both types of material were observed. From the result obtained, Steel 1006 shows better characteristic of withstanding impact failure  as compared to Al 2024 T4 in which von-Mises stress of Steel 1006 can withstand up to 1.21 GPa while Al 2024 T4 is 0.810 GPa.